1998
DOI: 10.1046/j.1365-2672.1998.00538.x
|View full text |Cite
|
Sign up to set email alerts
|

The microbiological examination of butchery products and butchers’ premises in the United Kingdom

Abstract: In a study of 1400 manufacturing butchers' premises, 2330 raw prepared meats, 2192 cooked meats and 4635 environmental samples were examined. Verocytotoxin-producing Escherichia coli O157:H7 (O157 VTEC) was isolated from five of 1400 (0.4%) premises. Three raw meat products contained O157 VTEC, and two raw meat preparation areas and two items of equipment used exclusively for cooked meats were contaminated with O157 VTEC. Salmonella spp. and Campylobacter spp. were detected in 84 of 2330 (4%) and 15 of 2330 (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
4
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 7 publications
2
33
4
1
Order By: Relevance
“…In this way Mortlock et al (1999) found signiWcant diVerences between food industries, retailers and caterers in UK, with a higher implementation level by food industries. Little and De Louvois (1998) identiWed a low level of application by butchers in the same country. Leitenberger and Röcken (1998) described major barriers in Germany on Good Hygiene Practices and HACCP implementation by bakeries.…”
Section: Business Demandmentioning
confidence: 99%
“…In this way Mortlock et al (1999) found signiWcant diVerences between food industries, retailers and caterers in UK, with a higher implementation level by food industries. Little and De Louvois (1998) identiWed a low level of application by butchers in the same country. Leitenberger and Röcken (1998) described major barriers in Germany on Good Hygiene Practices and HACCP implementation by bakeries.…”
Section: Business Demandmentioning
confidence: 99%
“…It was also discovered that the detergent used on the premises had no disinfectant bactericidal qualities. Little and de Louvois (1998) conducted a microbiological survey of butchery premises and products in the UK and isolated verocytotoxigenic E. coli 0157 from chopping surfaces, a weighing balance pan and meat slicer blades. It was not made clear the type of chopping surface involved; however, E. coli 0157 have been shown to become entrapped in the porous surface of wooden cutting boards and to remain viable on these materials for at least 12 h (Ak et al 1994).…”
Section: Survival On Surfacesmentioning
confidence: 99%
“…The com-pletion of the full genome sequence of this strain (3) has allowed the development of commercial DNA microarray chips, and the vast biological knowledge of this organism facilitates the interpretation of expression profiles from the microarray analysis. Other E. coli strains such as verotoxigenic E. coli O157:H7 are important human pathogens, and outbreaks have been caused by contaminated drinking water (15) and cross-contamination of foods probably due to improper disinfection of food process equipment (5,22). E. coli is therefore an important organism when the need arises to evaluate a potential antimicrobial agent.…”
mentioning
confidence: 99%